Comparison of patellofemoral contact pressure after semi-cylindrical recession trochleoplasty and trochlear block recession in feline cadavers - Choi, Goda; Kang, Jinsu; Kim, Namsoo; Heo, Suyoung (Frontiers in Veterinary Science, 2023)
The purpose of this study was to compare the changes in the patellofemoral joint (PFJ) contact mechanisms of the normal state, trochlear hypoplasia model and after performing trochleoplasty on the hypoplasia model in feline cadavers. 20 normal pelvic limbs were acquired from the 10 feline cadavers. First, the PFJ contact mechanisms are measured in normal state, trochlear hypoplasia models were created using customized trochlear ridge cutting guides. After measuring PFJ contact mechanisms in the trochlear hypoplasia models, they were divided into two groups and performed semi-cylindrical recession trochleoplasty (SCRT) and trochlear block recession (TBR) respectively. After that, the PFJ contact mechanisms were measured and the values of the 4 groups (normal state, trochlear hypoplasia, SCRT, TBR) were compared. The trochlear hypoplasia group was showed increased contact pressure and decreased contact areas compared to normal state group. In the groups that underwent tracheoplasty (SCRT and TBR), PFJ contact mechanisms were recovered similarly to that of the normal state group. The PFJ of the SCRP group was measured similar to that of the normal group than that of the TBR group. Tracheoplasty can be useful in restoring PFJ contact mechanisms and SCRT can be considered as a good alternative to the conventional methods of trochleoplasty.